Extracting the Essential Simplicity of the Internet: Looking past inessential complexities to explain the Internet's simple yet daring design. - MCCAULEY, JAMES; SHENKER, SCOTT; VARGHESE, GEORGE (Communications of the ACM, 2023)
The article focuses on the Internet's essential simplicity. The authors discuss the fundamental Internet design choices that have been in place since the 1980s, examines the rationale behind these design choices in an effort to understand the "why, not how" of the Internet, and offers insights for all computer scientists. A "Brief Internet Timeline" is also provided.